2021
DOI: 10.1155/2021/2648065
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Gastric Mucosa: The Dual Role and Potential Therapeutic Target

Abstract: The incidence of stomach diseases is very high, which has a significant impact on human health. Damaged gastric mucosa is more vulnerable to injury, leading to bleeding and perforation, which eventually aggravates the primary disease. Therefore, the protection of gastric mucosa is crucial. However, existing drugs that protect gastric mucosa can cause nonnegligible side effects, such as hepatic inflammation, nephritis, hypoacidity, impotence, osteoporotic bone fracture, and hypergastrinemia. Autophagy, as a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Scholars have confirmed that IFN-γ inhibits gastric carcinogenesis by inducing autophagy to reduce apoptosis of epithelial cells [ 96 ]. Therefore, the regulation of autophagy is expected to be a potential target for gastric mucosal protection [ 97 ].…”
Section: Pharmacological Mechanisms Of Tcm For the Treatment Of Cgmentioning
confidence: 99%
“…Scholars have confirmed that IFN-γ inhibits gastric carcinogenesis by inducing autophagy to reduce apoptosis of epithelial cells [ 96 ]. Therefore, the regulation of autophagy is expected to be a potential target for gastric mucosal protection [ 97 ].…”
Section: Pharmacological Mechanisms Of Tcm For the Treatment Of Cgmentioning
confidence: 99%
“…On the other hand, vacuolating cytotoxin A (VacA) adds to ROS production by activating nuclear factor kappa B (NFκB) through Ca2+ influx [ 14 ]. VacA inhibits autophagy in gastric epithelial cells while creating an environment prompting cancer pathogenesis [ 79 , 80 ] ( Table 1 ). Lastly, another virulence factor known as γ-glutamyltransferase in the bacteria releases many radical ions, further damaging gastric epithelial cells [ 81 ].…”
Section: Mechanisms Causing Gastric Cancer From the Synergistic Influ...mentioning
confidence: 99%
“…The main side effects of H2 receptor antagonists are nausea, vomiting, dizziness, dry mouth, constipation, and increased heart rate 12 . Almagate Suspension as a Gastric Mucosal Protectant is facing non-negligible side effects, including liver in ammation, nephritis, decreased acidity, impotence, osteoporotic fractures, and hyperglycaemia 13 . Commonly used antimicrobial drugs include amoxicillin and clarithromycin.…”
Section: Introductionmentioning
confidence: 99%